Hi good people!!!....

The sum is:

\(x-3 \sqrt{x+2}=2\)

when we solve x, we get x=14 or x=-1

-1 is rendered na, but 14, not---why is this?

If I replace x with -1, we get

\(-1-3 \sqrt{-1+2}=2\)

which is \(-4 \sqrt{1}=2\)

which is \(-4=2\)...which of course is NOT..

But the same goes for the 14??

\(14-3 \sqrt{14+2}=2\)

which is \(11 \sqrt{16}=2\)

which is \(44=2\)

which also is NOT???

all and any answer is very appreciated!..thank you all kindly.

juriemagic Oct 12, 2020

#1**0 **

-1` - 3 sqrt(-1+2) = 2 ????? no it does not...it equals -4

the solutions you obtained are both incorrect...you made a mistake somewhere (we ALL do !)

......go back and solve it again to get different answers

ElectricPavlov Oct 12, 2020

#2**+1 **

Update : I looked at it a little closer:

x-2 = 3 (sqrt(x+2)) square both sides

x^2 - 4x + 4 = 9 (x+2)

x^2 -13x -14 = 0

Quadratic equation shows x = -1 and 14

14 - 3 sqrt (14+2) = 2

14 - 3 (sqrt16) = 2 ( look at your step where you get 11 sqrt (16) <---- this is where you made your error)

14 - 12 = 2 so 14 IS an answer only -1 is NOT.

ElectricPavlov Oct 12, 2020

#3**+1 **

aawww, you know what I did?????...I did not follow the order of operations when I checked the roots.....Thank you for your time, I do appreciate..

juriemagic
Oct 12, 2020